PEMBELAJARAN ONLINE MENGGUNAKAN APLIKASI WHATSAPP (WA) MATA PELAJARAN BAHASA INDONESIA PADA MATERI MENYAJIKAN RINGKASAN TEKS EKSPLANASI DI KELAS 5 SD DALAM MASA PANDEMI COVID 19 - Verawati Harahap; Deden Herdiana Altaftazani (IKIP Siliwangi, 2022)
In online learning there are problems including problems with teachers, students, and parents of students. The objectives of this study include knowing the online learning scenario using the WhatsApp (WA) application, knowing the difficulties and obstacles faced by teachers and students, knowing the responses of teachers and students, knowing the teaching materials, lks, and assignments given, knowing what efforts the teacher should do so that online learning using the WhatsApp (WA) application can run more effectively. The WhatsApp (WA) application is a social media application for communicating, users can receive and send messages, photos, videos and files. During the Covid 19 pandemic, the WhatsApp (WA) application is very suitable for use in online learning. The subjects of this study were 12 grade students from 2 schools. The first school is at SDN 065 Cihampelas in Bandung City and the second is at SDN 031 Pelesiran Kota Bandung. The results of the problems found in online-based learning on explanatory text learning materials, students find it difficult to consult with the teacher, because the explanatory text requires clear explanations to find out the parts of the structure and the kinds of linguistic rules contained in the explanatory text. The conclusion of the success of this online learning requires full help and support from parents. The solution that can be done with online learning is collaboration between teachers, parents, and students. keywords: online learningusing the WhatsApp (WA) application, presents a summary of the explanatory text